Association of bone attrition with knee pain, stiffness and disability: a cross-sectional study. Issue 2 (24th September 2010) - Reichenbach, Stephan; Dieppe, Paul A; Nüesch, Eveline; Williams, Susan; Villiger, Peter M; Jüni, Peter
Abstract : Objectives: Bone pathologies as detected on MRI are associated with the presence of pain in knee osteoarthritis (OA). The authors examined whether bone attrition assessed on x-rays was associated with pain, stiffness and disability. Methods: The authors analysed x-rays of 1326 knees with OA from 783 individuals participating in the cross-sectional population-based Somerset and Avon Survey of Health. The diagnosis of OA was defined by the presence of osteophytes in anteroposterior (AP) or lateral views. Bone attrition was graded from 0 (no attrition) to 3 (severe attrition >10 mm) and Kellgren and Lawrence (K/L) scores were assigned on AP views. Logistic regression models adjusted for gender, age, body mass index, effusion and K/L scores were used to determine whether bone attrition was associated with pain, stiffness and disability. Results: Pain was reported in 84 knees (74%) with radiographic bone attrition compared with 505 (42%) without bone attrition (adjusted OR 2.22, 95% CI 1.29 to 3.80). The adjusted OR was increased for day pain but not for night pain (p for interaction <0.001). Stiffness was reported for 85 knees with bone attrition (75%) and 437 knees without (36%) (adjusted OR 3.23, 95% CI 1.85 to 5.64). Disability was reported by 40 individuals with bone attrition (50%) and 140 individuals without (24%) (adjusted OR 2.09, 95% CI 1.19 to 3.68). Conclusions: Bone attrition detected on conventional x-rays using a simple cheap technique is strongly associated with the presence of day pain, stiffness and disability in knee OA.